Generic structures and linguistic features of TESOL master’s thesis acknowledgements written by Vietnamese postgraduates - Nguyen Thi Thuy Loan (Penerbit Universiti Kebangsaan Malaysia, 2017)
Acknowledgements are a widely used genre in academic discourse to express gratitude towards various types of assistance and contribution of individuals and institutions, and they have been reported to be contextually and culturally interwoven. Despite a number of acknowledgement studies in various settings, little is known of how these texts are composed by EFL writers in Vietnam and whether or not the culture has any influence on the composition of acknowledgements as reported in previous studies of acknowledgements. Following Hyland’s (2004) and Hyland and Tse’s (2004) frameworks, this study investigates the generic structures and linguistic elements of acknowledgements in 202 TESOL master’s theses written by Vietnamese postgraduates. The findings were compared with those in the literature to explore cross-cultural variations in acknowledgement writing. Semi-structured interviews were also conducted with actual thesis writers. The results revealed that these writers generally followed Hyland’s (2004) three-tier structure of writing thesis acknowledgements, but they were frank and less reserved in expressing their gratitude than their Chinese-speaking counterparts. Moreover, socio-cultural expectations, personal dispositions, and individual writing styles mainly affected their move constructions, inclusions of acknowledgees and linguistic choices.